Internet as educational electronic communication media “A study for testing electronic education in Iraq universities during covid-19 pandemic” - Mohammed Raffia Labid Alrawi (Journal of Madenat Alelem University College, 2022)
The world was recently exposed to a major crisis that affected all aspects of life and changed many of the processes that the world used to practice naturally. After the spread of the Corona pandemic, which suddenly invaded the world and turned the scales, because this pandemic or this virus is a new type that humanity has never dealt with, at the different level of its health, technical and service development, so major countries have become unable to confront this dangerous disease at the beginning of its appearance and until recently, which negatively affected many institutions, including educational institutions, which are characterized by direct confrontational contact in the nature of their work, and this helps to spread the disease and expose the human being to an imminent danger that may lead to death, which necessitates relying on another type of education, which is (e-learning), which is a new method of education in most Iraqi universities and requires skills that may not be available to everyone, whether students, faculty, or anyone working in educational institutions. From here the idea of ​​our research came to life, to see the effects of this experience and its efficiency in Iraqi universities and to know the positive and negative effects and the effectiveness of this type of education and its efficiency and the level of benefit achieved from it. This research included three sections; the first section dealt with the methodological framework of the research. The second section talked about e-learning and the importance of e-learning, its characteristics, features, and patterns of e-learning, in addition to the benefit achieved by e-learning in the field of education. As for the third section, it was devoted to the practical aspect, which is represented in the analysis and interpretation of data, which were collected through an electronic form that was distributed to all Iraqi universities and was a research community.